2022
DOI: 10.1111/jfpe.14146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operating parameters on performance of finger millet pearling machine

Abstract: The effect of operational parameters such as feed rate (FR), drum speed (DS), and concave clearance (CC) was studied on the performance of a pearling drum. The pearling drum consists of pearling cylinder, pearling sieve, concave, and outer casing of the drum. The response surface method with CCRD experimental design was used to study the effect of operational parameters on pearling drum. The considered levels for optimizing operational parameters viz., FR, DS, and CC were 40–80 kg/h, 5–10 m/s, and 3–15 mm, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The performance of millet pearling machines is affected by various operating parameters such as feed rate, clearance, and rotational speed. Powar et al (2022) showed that optimizing these parameters can enhance the efficiency of the pearling process and increase the yield of millet flour.…”
mentioning
confidence: 99%
“…The performance of millet pearling machines is affected by various operating parameters such as feed rate, clearance, and rotational speed. Powar et al (2022) showed that optimizing these parameters can enhance the efficiency of the pearling process and increase the yield of millet flour.…”
mentioning
confidence: 99%